MARKETING MIX RELATIONSHIP ANALYSIS ON OUTPATIENT LOYALTY AT SOUTH TANGERANG CITY GENERAL HOSPITAL IN 2023 - Deviliena Assyifa; Noor Latifah; Fini Fajrini; Hardiman SG (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Observing the high volume of patient visits, particularly in outpatient facilities, and the number of hospital contests in Indonesia. Therefore, in order to keep patients loyal to the hospital and make sure that their health treatments are in line with their target market, hospitals need to create marketing plans. One of them uses the marketing mix as a strategy to accomplish its objectives. Product, price, place, promotion, person, method, and tangible evidence are the seven components of marketing mixes. According to data on outpatient visits to South Tangerang City Hospital, there was a notable decline of 173,653 visits in 2019, followed by 119,020 visits in 2020 and 103,643 visits in 2021. However, there was an increase of 124,618 visits in 2022. Finding out how the marketing mix and outpatient loyalty at South Tangerang City Hospital in 2023 relate to one another was the aim of this study. Using a cross-sectional methodology and an outpatient sample, this study was carried out at South Tangerang City Hospital between February and June 2023. Purposive sampling was used to select 120 respondents for the sample. The chi-square test was used for the bivariate analysis. Seven marketing mix variables—product (pvalue=0.000), price (pvalue=0.000), place (pvalue=0.014), promotion (pvalue=0.000), person (pvalue=0.004), process (pvalue=0.000), and physical evidence (pvalue=0.002)—and their relationship to outpatient loyalty at South Tangerang City Hospital in 2023.